Relationships between illness perception, functional status, social support, and self-care behavior among Thai people at high risk of stroke: A cross-sectional study - Surachai Maninet; Chalermchai Desaravinid (Belitung Raya Foundation, Indonesia, 2023)
Background: People at high risk of stroke reported having difficulty performing self-care behavior. Although the literature has identified various factors related to self-care behavior in this population; however, there is a lack of studies to conclude the associated antecedents of self-care behavior, particularly in Thailand. Objective: This study aimed to examine the relationships between illness perception, functional status, social support, and self-care behavior among people at high risk of stroke. Methods: A correlational cross-sectional study design was used. One hundred and seventy people at high risk of stroke were selected from ten health-promoting hospitals in the Northeast region of Thailand using multi-stage sampling. Data were gathered using self-report questionnaires, including the brief illness perception questionnaire, functional status scale, multidimensional scale of perceived social support, and self-care behavior questionnaire, from November 2021 to February 2022. Data were analyzed using mean, standard deviation, and Pearson’s product-moment correlation. Results: One hundred percent of the participants completed the questionnaires. The participants had a moderate level of self-care behavior (M = 64.54, SD = 7.46). Social support and functional status had medium positive significant correlations with self-care behavior among people at high risk of stroke (r = 0.460 and r = 0.304, p <0.01), respectively. In contrast, illness perception had a small negative significant correlation with self-care behavior among people at high risk of stroke (r = -0.179, p <0.05). Conclusion: Social support, functional status, and illness perception are essential factors of self-care behavior among people at high risk of stroke. The findings shed light that nurses and other healthcare professionals should promote self-care behavior in these people by enhancing them to maintain proper functioning, positive illness-related perception, and family members' involvement. However, further study is needed to determine a causal relationship between these factors with self-care behavior.